2020
DOI: 10.1093/mnras/staa695
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic analysis of accretion/ejection signatures in the Herbig Ae/Be stars HD 261941 and V590 Mon

Abstract: Herbig Ae/Be (HAeBe) stars are the intermediate-mass analogues of low-mass T Tauri stars. Both groups may present signs of accretion, outflow, and IR excess related to the presence of circumstellar discs. Magnetospheric accretion models are generally used to describe accreting T Tauri stars, which are known to have magnetic fields strong enough to truncate their inner discs and form accretion funnels. Since few HAeBe stars have had magnetic fields detected, they may accrete through a different mechanism. Our g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 107 publications
1
12
0
Order By: Relevance
“…Analogous spectro-interferometric studies devoted to fainter T Tauri stars are less frequent (see e.g., [75,76]), but in fact their emission line profiles are currently reproduced using hybrid models that consider magnetically driven accretion and winds (e.g., [33,34]). Similarly, the emission line profiles of HAeBes can also be reproduced either from MA modeling alone or combined with magnetically driven winds [56,61,74,[77][78][79][80][81]. Nonetheless, although many of these models are natural extensions from previous devoted to CTT stars, they lack a careful treatment of the larger projected rotational velocities that are characteristic of many HAeBes, which still constitutes a major limitation for the applicability of MA line modeling in these objects [28,74,81].…”
Section: Is Magnetospheric Accretion Plausible For Herbig Ae/be Stars?mentioning
confidence: 99%
See 2 more Smart Citations
“…Analogous spectro-interferometric studies devoted to fainter T Tauri stars are less frequent (see e.g., [75,76]), but in fact their emission line profiles are currently reproduced using hybrid models that consider magnetically driven accretion and winds (e.g., [33,34]). Similarly, the emission line profiles of HAeBes can also be reproduced either from MA modeling alone or combined with magnetically driven winds [56,61,74,[77][78][79][80][81]. Nonetheless, although many of these models are natural extensions from previous devoted to CTT stars, they lack a careful treatment of the larger projected rotational velocities that are characteristic of many HAeBes, which still constitutes a major limitation for the applicability of MA line modeling in these objects [28,74,81].…”
Section: Is Magnetospheric Accretion Plausible For Herbig Ae/be Stars?mentioning
confidence: 99%
“…Similarly, the emission line profiles of HAeBes can also be reproduced either from MA modeling alone or combined with magnetically driven winds [56,61,74,[77][78][79][80][81]. Nonetheless, although many of these models are natural extensions from previous devoted to CTT stars, they lack a careful treatment of the larger projected rotational velocities that are characteristic of many HAeBes, which still constitutes a major limitation for the applicability of MA line modeling in these objects [28,74,81]. Other direct and indirect observational tests mentioned in the previous section that were important to support MA in CTTs can hardly be applied to HAeBes.…”
Section: Is Magnetospheric Accretion Plausible For Herbig Ae/be Stars?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although V590 Mon has been considered an accreting source in the past, this could be associated with the significant variability of this star on timescales of decades (Pérez et al 2008;Moura et al 2020, and references therein). Indeed, the more recent work by Moura et al (2020) shows that the Hα emission currently shown by V590 Mon is associated to outflowing material in a disk wind and that accretion has a negligible contribution to its Hα line profile. A companion at > 5 ′′ from the central object and fainter by 6.6 magnitudes in the Kband was reported by Thomas et al (2007).…”
Section: V590 Monmentioning
confidence: 99%
“…V590 Mon (aka LkHa 25, Walker 90) is a HBe star with a stellar temperature of ∼ 12500 K and mass of ∼ 3 M ⊙ (Fairlamb et al 2015;Moura et al 2020). A distance of 689 +57 −49 pc is inferred from the recent Gaia EDR3 parallax (Lindegren et al 2020).…”
Section: V590 Monmentioning
confidence: 99%